2018
DOI: 10.1016/j.jcou.2018.04.016
|View full text |Cite
|
Sign up to set email alerts
|

Standing out the key role of ultramicroporosity to tailor biomass-derived carbons for CO2 capture

Abstract: The successful tailoring of the ultramicroporosity remarkably increases the CO2 uptake capacity of low cost-carbons derived by a simple one-pot physical activation of olive stones, coffee grounds, almond shells and grape seeds. A porous network dominated by ~40-46% of ultramicropores below 0.5 nm and no significant presence of pores above 0.7 nm boosts the CO2 uptake at 1 bar and 298 K around 40% compared to materials with similar micropore volume. A slight ultramicropore widening causes the drop to a standard… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 37 publications
0
29
0
Order By: Relevance
“…Table 6 shows the CO 2 adsorption capacities of activated carbons prepared in this work, the range of this parameter is from 205 to 333 mg g −1 , these data are satisfactory, considering the fact that in other studies the adsorbed amounts have been between 43 and 400 mg g −1 in adsorbent materials such as: zeolites, carbon fibers, MOF and activated carbon (Plaza et al, 2010 , Carruthers et al, 2012 ; Cho et al, 2012 ; Sevilla and Fuertes, 2012 ; Wahby et al, 2012 ; Yang et al, 2012 ; An et al, 2013 ; Liu et al, 2013 ; Jang et al, 2018 ; Querejeta et al, 2018 ). Taking into account the CO 2 adsorption capacities of the prepared activated carbon, it can be affirmed that the modifications made with HNO 3 and NH 4 OH were effective since they generated an increase of up to 61.56% in the adsorbed amount of this gas on the carbonaceous materials, This increase is associated with the incorporation of nitrogen groups that act as electron donors and carboxylic groups that are capable of establishing Lewis acid-base interactions with the CO 2 molecule, because these groups not only have a carbonyl group that can act as a Lewis base toward the carbon atom (Lewis acid) of the molecule, but also has an acidic proton that can act as a Lewis acid toward the oxygen atom (Lewis bases) of the CO 2 molecule (Bell et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…Table 6 shows the CO 2 adsorption capacities of activated carbons prepared in this work, the range of this parameter is from 205 to 333 mg g −1 , these data are satisfactory, considering the fact that in other studies the adsorbed amounts have been between 43 and 400 mg g −1 in adsorbent materials such as: zeolites, carbon fibers, MOF and activated carbon (Plaza et al, 2010 , Carruthers et al, 2012 ; Cho et al, 2012 ; Sevilla and Fuertes, 2012 ; Wahby et al, 2012 ; Yang et al, 2012 ; An et al, 2013 ; Liu et al, 2013 ; Jang et al, 2018 ; Querejeta et al, 2018 ). Taking into account the CO 2 adsorption capacities of the prepared activated carbon, it can be affirmed that the modifications made with HNO 3 and NH 4 OH were effective since they generated an increase of up to 61.56% in the adsorbed amount of this gas on the carbonaceous materials, This increase is associated with the incorporation of nitrogen groups that act as electron donors and carboxylic groups that are capable of establishing Lewis acid-base interactions with the CO 2 molecule, because these groups not only have a carbonyl group that can act as a Lewis base toward the carbon atom (Lewis acid) of the molecule, but also has an acidic proton that can act as a Lewis acid toward the oxygen atom (Lewis bases) of the CO 2 molecule (Bell et al, 2003 ).…”
Section: Resultsmentioning
confidence: 99%
“…RN2K shows an average narrow micropore size of 0.69 nm, which has been pointed out as very suitable for CO 2 adsorption at post-combustion capture conditions [33][34][35][36][37][38][39] . However, even though it has been demonstrated that pore size governs CO 2 adsorption at low pressures [33][34][35][36][37] , the reduction of the narrow micropore volume ( W 0 , CO2 ) certainly penalizes the adsorption of CO 2 on RN2K.…”
Section: Pore Structure Characteristicsmentioning
confidence: 98%
“…The considerable share of micropores, and in particular, the rise in the amount of supermicropores therefore makes carbonization pressure a parameter of interest when production of materials for various new applications, including double-layer electric capacitors, is concerned [20]. The relatively high share of ultramicropores reported for materials developed under pressurized conditions may be considered advantageous in the potential applications of carbon materials for CO 2 capture [28].…”
Section: Resultsmentioning
confidence: 99%
“…It also contains high amounts of phenolics, mainly hydroxytyrosol and its derivatives, with environmentally undesired phytotoxic effects [13]. Various research studies examining the application of olive stones [14,15,16,17,18] and, less extensively, of olive tree pruning residues [19,20] or mill waste [21,22,23,24,25,26] as activated carbon precursors are available in the literature, reporting their physical and chemical treatment effects and applicability in CO 2 , NO 2 , CH 4 , and gasoline vapors capture [27,28,29,30,31,32], as well as for dyes and heavy metals removal from aqueous solutions [21,24,25,26]. The activation of a raw precursor usually involves chemical treatment with acidic and/or alkali agents, like H 2 SO 4 [31], H 3 PO 4 [19,21,23,30,31], or KOH [20,23,31], followed by carbonization under inert gas atmosphere at an increased temperature, typically of 350–800 °C.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation